The self divided: the problems of contradictory claims to Indigenous peoples' self-determination in Australia. Issue 1 (7th February 2019) - Young, Stephen M.
ABSTRACT: When the United Nations General Assembly endorsed the United Nations Declaration on the Rights of Indigenous Peoples (' UNDRIP ') in 2007, many extolled it for recognising Indigenous peoples' right of self-determination. Although there is some consensus that all peoples have self-determination, as a legal claim it has routinely inspired criticism that it will lead to contradictory claims, interpretations, and further political contestation. Ten years after UNDRIP 's endorsement, some Indigenous claims of self-determination in Australia are contradictory. While contradictory claims may not be inherently problematic, in the context explored in this article, there are problematic effects. This article examines how contradictory self-determination claims arose in response to Australia's recent Native Title Amendment (Indigenous Land Use Agreements) Act 2017 (Cth) (' 2017 Amendments '), which amended and weakened the Native Title Act 1993 (Cth) ('NTA') . It also evaluates the consequences of those contradictory claims and argues for renewed critical assessment of who legitimately determines the self who claims self-determination.